Cardiovascular disease risk factors and women prisoners in the UK: the impact of imprisonment. - Plugge, E; Foster, C; Yudkin, P; Douglas, N (2009)
Cardiovascular disease (CVD) is a leading cause of death throughout the world. In high income countries, the greatest burden of disease is seen in those from lower socio-economic groups. It is therefore likely that CVD is an important issue for prisoners in the UK, the majority of whom were either unemployed or in non-skilled employment prior to imprisonment. However, there is little research examining this issue. The aim of this study was to examine the prevalence of five modifiable cardiovascular risk factors (smoking, physical activity, diet, body mass index and hypertension) in women prisoners on entry to prison and then 1 month after imprisonment. This was a prospective longitudinal study involving 505 women prisoners in England. Participants completed a questionnaire containing questions about health-related behaviours within 72 h of entering prison. The researchers measured their blood pressure, height and weight. They followed up all participants who were still imprisoned 1 month later and invited them to participate again. The results showed that women prisoners were at high risk of CVD in the future; 85% smoked cigarettes, 87% were insufficiently active to benefit their health, 86% did not eat at least five portions of fruit and vegetables each day and 30% were overweight or obese. After 1 month, there were few improvements in risk factors. This may in part reflect the fact that, unlike prisons in other high income countries, there are currently no systematic approaches which address these health issues within UK women's prisons.